2003
DOI: 10.1083/jcb.200209074
|View full text |Cite
|
Sign up to set email alerts
|

AMIGO, a transmembrane protein implicated in axon tract development, defines a novel protein family with leucine-rich repeats

Abstract: Ordered differential display identified a novel sequence induced in neurons by the neurite-promoting protein amphoterin. We named this gene amphoterin-induced gene and ORF (AMIGO), and also cloned two other novel genes homologous to AMIGO (AMIGO2 and AMIGO3). Together, these three AMIGOs form a novel family of genes coding for type I transmembrane proteins which contain a signal sequence for secretion and a transmembrane domain. The deduced extracellular parts of the AMIGOs contain six leucine-rich repeats (LR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
203
2
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 145 publications
(216 citation statements)
references
References 36 publications
(43 reference statements)
7
203
2
2
Order By: Relevance
“…Thus, a YAF2 deletion may have caused the growth retardation and/or hypotonicity in the two patients. As AMIGO2 is highly expressed in the nervous system and plays a role in growth of axonal connection and myelination (Kuja-Panula et al 2003); its deletion can cause psychomotor developmental delay.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, a YAF2 deletion may have caused the growth retardation and/or hypotonicity in the two patients. As AMIGO2 is highly expressed in the nervous system and plays a role in growth of axonal connection and myelination (Kuja-Panula et al 2003); its deletion can cause psychomotor developmental delay.…”
Section: Resultsmentioning
confidence: 99%
“…The amino acid alignment among the AMI GO family revealed that the binding of the C-terminal region of AMI GO2 to the PH domain of PDK1 is highly conserved, although the amino acid homologies between AMI GO2 and AMI GO1 and between AMI GO2 and AMI GO3 are both 48% (Kuja-Panula et al, 2003). The similarity of the binding sequence to the PH domain indicates that PDK1 is also likely to interact with AMI GO1 and AMI GO3 expressed in a variety of cell types.…”
Section: Discussionmentioning
confidence: 99%
“…The forward and reverse murine AMI GO2 primers were 5′-GGC ACTTT AGCTC CGTGA TG-3′ and 5′-GTC TCGTT TAACA GCCGC TG-3′, respectively, as previously described (Kuja-Panula et al, 2003). For the mouse GAP DH control, the forward and reverse primers were 5′-CAA CGACC CCTTC ATTGA CC-3′ and 5′-AGT GATGG CATGG ACTGT GG-3′, respectively.…”
Section: Rt-pcr and Real-time Pcr Primersmentioning
confidence: 99%
See 2 more Smart Citations